Comparison Between the Development of Arabic Linguistics and Modern Linguistics - Yulia Zulpathul Aizza; Moch Mu'izzuddin; Ahmad Suhaili; Rohanda Rohanda (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Arabic linguistics is a branch of science that focuses on the study of Arabic from various fields, namely phonology, morphology, syntax, and semantics. Since classical times, Muslim scholars have developed linguistic theories that have contributed greatly to understanding the structure of the Arabic language. In its further development, Arabic linguistics began to interact with modern linguistic approaches, which offer more systematic and comprehensive analysis methods. Modern linguistics, which includes various branches such as structuralism, sociolinguistics, psycholinguistics, and discourse analysis, provides a new perspective in understanding Arabic, both in theoretical and applied aspects. The influence of this modern approach not only enriches the study of Arabic linguistics, but also supports the development of language technology, translation, and Arabic language learning for foreign speakers. This article aims to examine the development of Arabic linguistics from traditional to modern perspectives and to explore the scope of modern linguistics that has an impact on Arabic language studies in the contemporary era. Through a descriptive and analytical approach, this article identifies the role of modern linguistics in expanding the scope of Arabic language studies, resulting in a deeper understanding of the structure and function of the language in various contexts.